Growth and yield of Pleurotus Ostreatus using sugarcane bagasse as an alternative substrate in Malaysia - Fathie, Ahmad Zakil; K H, Muhammad Hassan; M Shafiq, Mohd Sueb; Ruzinah, Isha (IOP Publishing, 2020)
This paper looks at the feasibility of using sugarcane bagasse (SGB) for the cultivation of Pleurotus ostreatus (oyster mushrooms) as an alternative for rubber tree sawdust (RS). Three different compositions of oil palm trunk and rubber tree sawdust were studied with each composition having three replicates. A substrate containing only rubber tree sawdust acted as the control variable. The substrates were supplemented with 5% rice bran and 1.5% calcium carbonate. There are four steps involved in the cultivation of P. ostreatus which were bagging, sterilization, spawning and harvesting the substrates. The mycelia growth, spawn run, pin head formation, yield and biological efficiency were observed. The 100% composition of RS gave the best yield in terms of the mean height of stipe, which was 7.75cm. The mean fresh weight of sawdust was the highest with 50.4g with the number of fruiting bodies around 6. The least yield was recorded for 50% composition of substrates with a mean height of stipe 9.12cm. Among the substrates used, the RS showed the highest biological efficiency with 56.3% followed by 45.1% and 44.8% RS having mixed compositions of 25% and 50% SGB substrates, respectively. Hence, it is proven that in terms of quantity and quality, the unmixed substrates produced better edible mushrooms. However, the results obtained by SGB also showed a great potential as an alternative substrate for the cultivation of P. ostreatus when mixed with RS.